Evaluation of Damage Mechanisms and Skin Factor in Tight Gas Reservoirs - Bahrami, Hassan; Rezaee, M. Reza; Nazhat, D.; Ostojic, J. (Australian Petroleum Production and Exploration Association, 2011)
Tight gas reservoirs normally have production problems due to very low matrix permeability and significant damageduring well drilling, completion, stimulation and production. Therefore, they may not flow gas at optimum rateswithout advanced production improvement techniques. The main damage mechanisms and the factors that have significant influence on total skin factor in tight gas reservoirs include: mechanical damage to formation rock; plugging of natural fractures by mud solid particle invasion; relative permeability reduction around wellboreas a result of filtrate invasion; liquid leak-off into the formation during fracturing operations; water blocking;skin due to wellbore breakouts; and the damage associated with perforation. Drilling and fracturing fluids invasionmostly occurs through natural fractures and may also lead to serious permeability reduction in the rock matrix thatsurrounds the natural or hydraulic fractures. This study represents an evaluation of different damage mechanisms in tight gas formations, and examines the factors that can have significant influence on total skin factor and well productivity. Reservoir simulation was carried out based on a typical West Australian tight gas reservoir to understand how well productivity is affected by each of the damage mechanisms, such as natural fracture plugging, mud filtrate invasion, water blocking and perforation. Furthermore, some damage prevention and productivity improvement techniques are proposed, which can help improve well productivity in tight gas reservoirs.